POLA ALIRAN PANAS BERDASARKAN ANALISIS FLUIDA DAN MINERAL UBAHAN DI DAERAH PANAS BUMI SORIK MARAPI, KABUPATEN MANDAILING NATAL, PROVINSI SUMATRA UTARA: HEAT FLOW PATTERN BASED ON ANALYSIS OF GEOTHERMAL FLUID AND ALTERATION MINERAL IN SORIK MARAPI REGION, MANDAILING NATAL DISTRICT, NORTH SUMATRA PROVINCE - Azizi, Hisyam Azhar; Agus Didit Haryanto; Johanes Hutabarat; Dicky Muslim; Dewi Gentana; Ryan Hidayat (Buletin Sumber Daya Geologi, 2020)
Sorik Marapi geothermal area in Mandailing Natal Regency, North Sumatra Province has a high-temperature geothermal system that is interpreted from the chemical characteristics of hot springs. The presence of alteration minerals such as epidot in exploration well cutting samples strengthens the estimated reservoir temperature reaches 235â°C. The presence of hot water are more acidic hot spring around fumaroles and the minerals obtained from the drill well reflect the upflow zone while the hot spring group of neutral chloride water in the north with lower elevation reflects the outflow zone of the geothermal system here. This is a characteristic of hot fluid flow that occurs in geothermal areas of volcanic systems with steep terrain as well as Sorik Marapi area.